2018
DOI: 10.4103/sjg.sjg_49_18
|View full text |Cite
|
Sign up to set email alerts
|

Real-world single-center experience with entecavir and tenofovir disoproxil fumarate in treatment-naïve and experienced patients with chronic hepatitis B

Abstract: Background/Aim:The goal of antiviral therapy for chronic hepatitis B (CHB) is to improve survival of the patients by achieving a complete virological response (CVR). This study aimed to evaluate long-term efficacy of entecavir (ETV) and tenofovir disoproxil fumarate (TDF) in nucleos(t)ide analog (NA)-naïve and NA-experienced Korean patients with CHB and to determine the incidence of cirrhosis-related complications in these patients.Patients and Methods:We retrospectively reviewed medical records of all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These clinical studies demonstrated results comparable to those of ETV or TDF, suggesting that TAF is non‐inferior to a first‐line NA treatment 14,15,24 . However, the results of the studies should be interpreted with caution due to bias in favor of groups with shorter observation periods, as TAF has only been used to treat CHB in recent years 7,25,26 . Similarly, recent controversy about the efficacy of ETV and TDF against HCC development and other liver‐related complications has been largely attributed to key confounders, such as varying observation periods, time differences over the years, and gradual improvements in the efficacy of curative treatments over time 27–30 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These clinical studies demonstrated results comparable to those of ETV or TDF, suggesting that TAF is non‐inferior to a first‐line NA treatment 14,15,24 . However, the results of the studies should be interpreted with caution due to bias in favor of groups with shorter observation periods, as TAF has only been used to treat CHB in recent years 7,25,26 . Similarly, recent controversy about the efficacy of ETV and TDF against HCC development and other liver‐related complications has been largely attributed to key confounders, such as varying observation periods, time differences over the years, and gradual improvements in the efficacy of curative treatments over time 27–30 .…”
Section: Discussionmentioning
confidence: 89%
“…14,15,24 bias in favor of groups with shorter observation periods, as TAF has only been used to treat CHB in recent years. 7,25,26 Similarly, recent controversy about the efficacy of ETV and TDF against HCC development and other liver-related complications has been largely attributed to key confounders, such as varying observation periods, time differences over the years, and gradual improvements in the efficacy of curative treatments over time. [27][28][29][30] In the present study, the results were obtained after adjusting for these major confounders, which was considered a valid method for evaluating NA's efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Kim YM et al [79] monitored the virological response (HBV DNA level of less than 20 IU/mL) in HBV patients who had not received any antiviral treatment before and in patients who had previously tried another antiviral and developed resistance (antivirals such as lamivudine, adefovir). It was observed that treatment-naive patients achieved virological response much faster: 12.3 ± 10.5 months compared to 20.7 ± 27.4 months in experienced NA patients (p = 0.138).…”
Section: Clinical Results With Current Antiviral Medicationmentioning
confidence: 99%
“…Thus, although 50,027/119,053 (42.0%) patients in the meta-analysis were missed in the Elicit search, only 1 (596 patients) out of 9 comparative studies was missed. 4 Of the 37 additional papers “gained,” only 1 was an original research article (303 patients) 5 , which would have met our study criteria.…”
mentioning
confidence: 99%